OC-083 Faecal Occult Blood test Analysis in the United Kingdom Bowel Cancer Screening Programme. (4th June 2013) - Geraghty, J; Snowball, J; Butler, P; Sarkar, S; Blanks, R; Halloran, S; Rees, C
Abstract : Introduction: Increased vascularity of colorectal neoplasia creates bleeding detected by Faecal Occult Blood tests (FOBt). As bleeding is sporadic & unevenly distributed within stools, multiple testing may be required. UK bowel cancer screening programme (BCSP) kits contain 6 windows & subjects returning 5 or 6 positive results are termed "Abnormal" & referred to colonoscopy. If 1–4 windows are positive, the result is initially "Unclear" & 2 further kits are submitted, further positivity leads to colonoscopy ("Weak positive"). If no further blood is detected, subjects are deemed "Normal" & retested in 2 years. Aim: to study FOBt positivity in detail & whether particular patterns are associated with neoplasia rates that indicate the screening algorithm should be changed. Methods: We selected all subjects from one hub completing 2 screening episodes between 2007–9. Each episode included up to 3 kits and 18 windows. 95 possible combinations were identified. The number of positive windows compared to the total in a given episode was expressed as a "positivity ratio", ranging from 0–100%. Each combination leading to colonoscopy was analysed. Abnormal (83–100% positivity) & Unclear (11–83% positivity) groups were matched to neoplasia detection rates. Subjects with cancer detected in episode 2 following an Unclear result in episode 1, had their episode 1 pattern analysed. Results: FOBt from 284, 387 subjects resulted in 4, 000 colonoscopies, diagnosing 286 cancers. The overall cancer rate was 7.1% & adenoma rate 39.9%. The cancer rate was 21.3% in the Abnormal group and 5.8% in the Weak positive group. Cancer detection increased from 1.9–24.5% in linear correlation with increasing positivity of windows, ranging from 11–83% of windows positive. Equivalent percentage positivity rates may or may not lead to colonoscopy depending on the particular pattern. A combination of 4 positive windows in kit 1 followed by 2 normal kits (4NN) equates to a positivity rate of 22% & is currently categorised in the Normal group & doesn't lead to colonoscopy. Other combinations with 22% window positivity do lead to colonoscopy & a cancer detection rate of 3%. There were 260 subjects with a 4NN combination in episode 1 not leading to colonoscopy & 5 of these subsequently had cancers detected following different combinations in episode 2. Conclusion: This study demonstrates higher ratios of positive windows; detect higher rates of cancer. At present, in the UK some subjects with 11% positive windows proceed to colonoscopy, while others with a rate of 22% (all at kit 1) do not. Based on these findings, further work examining the entire BCSP population, including the costs & benefits of changing the algorithm is in progress. Disclosure of Interest: None Declared